Pancreatic Tuberculosis: Current Update on Clinical Manifestation and Diagnostic Modalities - Samudra Andi Yusuf; Hasan Maulahela; Anjar Raraswati; Maureen Irawati Koesnadi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Pancreatic tuberculosis is a very rare disease in either immunocompetent or immunocompromised hosts.The incidence of pancreatic tuberculosis was reported to be less than 4.7% in an autopsy series on tuberculosis patients in 1944 and 2% in another autopsy series in 1966.Despite that, in recent times, an increase in the number of reports of pancreatic TB has been noted.This condition is possibly caused by an improvement in diagnostic imaging tools, the development of different techniques that make obtaining specimens from the pancreas possible, and an increase in HIV prevalence worldwide. Therefore, this review article discusses the current update in the clinical manifestations and diagnostic modalities of pancreatic tuberculosis.Pancreatic tuberculosis is a very rare condition with a various range of non-specific clinical presentation and image features overlapping with those seen in pancreatic neoplasia. A combination of diagnostic modalities should be done to establish a diagnosis of pancreatic tuberculosis. Currently, direct histopathological examination is the best way of diagnosing tuberculosis. US/CT/EUS-guided biopsy is the recommended diagnostic technique. Most patients with pancreatic tuberculosis respond well to anti-tuberculosis drugs.